CD4+ beta islet cell-reactive T cell clones that suppress autoimmune diabetes in nonobese diabetic mice (The Rockefeller University Press, 1995)
We report the isolation of a panel of CD4+ T helper type 1 autoreactive T cell clones from the spleen of unprimed nonobese diabetic mice, a murine model of human insulin-dependent diabetes mellitus. The T cell clones express a diverse repertoire of T cell receptors, three of which recognize beta islet cell autoantigen(s). The islet cell-reactive T cell clones inhibit adoptive transfer of insulin-dependent diabetes mellitus and intraislet lymphocytic infiltration. The protective capacity of the T cell clones correlates with their ability to produce a novel immunoregulatory activity that potently inhibits in vitro allogeneic mixed lymphocyte reaction. The partially purified activity significantly inhibited the adoptive transfer of diabetes. Our work provides evidence in support of the existence of T helper type 1, CD4+ T cells reactive to beta islet cell autoantigens that have acquired a protective instead of a diabetogenic effector function. These T cells mediate their protective action in part by production of an immunoregulatory activity capable of down-regulating immune responses, and they are likely to represent a population of regulatory T cells that normally plays a role in maintaining peripheral tolerance.